Strong Positive Correlation between Neutrophil-to-lymphocyte Ratio and C-reactive Protein in Early Onset Sepsis - Ghrahani, Reni; Yuniati, Tetty; Judistiani, Raden Tina Dewi; Setiabudiawan, Budi (Faculty of Medicine, Universitas Padjadjaran, 2019)
Sepsis is a life-threatening disease with a high number of mortality in premature infants. Premature infants have immature immune systems, with less pool neutrophils and imperfect ability to destroy pathogen. Neutrophil function is supported by lymphocyte’s ability to form antibody or specific cell-surface receptors for particular antigens. This underlies the use of neutrophil-to-lymphocyte ratio (NLR) as an inflammation marker to detect and assess the severity of sepsis. C-reactive protein (CRP) is known as an acute phase reactant. Neutrophil-to-lymphocyte ratio is an easier, fast, and inexpensive method when compared to CRP. The aim of this study was to evaluate the correlation between NLR and CRP in detecting early-onset sepsis (EOS) in premature infants. A cross-sectional study was conducted on 53 premature infants born and hospitalized in a hospital in Indonesia who were recruited during the period of April to October 2018. Blood was sampled from the umbilical cord at birth for laboratory examination. The NLR was determined as the ratio of neutrophil to lymphocyte count. The Tollner scoring system was used to identify sepsis. Mann Whitney-U test and Spearman Correlation test were computed for the statistical analysis. neutrophil-to-lymphocyte ratio which results showed a strong positive correlation with CRP (r= 0.702, 0=0.001) in premature infants with EOS. Leukocyte count was lower in infants with EOS than those without EOS group (median; IQR, x103: 8.9 (6.3-13.8) vs 12.5 (10.1- 16.1); p=0.016). Neutrophil-to-lymphocyte ratio and CRP tended to be lower in EOS group when compared to that of the non-EOS group. In conclusion, NLR has a strong positive correlation with CRP in premature infants with EOS. Korelasi Positif Kuat antara Neutrophil-to-lymphocyte dan C-reactive protein pada Sepsis Awitan DiniSepsis pada bayi prematur adalah keadaan mengancam jiwa dengan mortalitas tinggi. Bayi prematur memiliki sistem imun imatur, sedikit persediaan neutrofil serta fungsi belum sempurna untuk melawan patogen. Fungsi neutrofil didukung limfosit membuat antibodi serta reseptor permukaan spesifik untuk antigen tertentu. Neutrophil-to-lymphocyte ratio (NLR) diajukan untuk petanda inflamasi, mendeteksi dan menentukan derajat sepsis, sedangkan C-reactive protein (CRP) telah diketahui sebagai protein fase akut. Neutrophil-to-lymphocyte ratio adalah pemeriksaan yang lebih mudah, cepat, murah dibandingkan dengan CRP. Penelitian potong lintang ini bertujuan mengevaluasi korelasi NLR dengan CRP untuk mendeteksi sepsis awitan dini pada 53 bayi prematur, yang lahir dan dirawat di rumah sakit kami, selama April-Oktober 2018. Sampel darah dari tali pusat pada saat lahir. Neutrophil-to-lymphocyte ratio adalah rasio jumlah neutrofil terhadap limfosit. Skoring Tollner digunakan untuk mengidentifikasi sepsis. Analisis statistik menggunakan Uji Mann-Whitney dan korelasi Spearman. Korelasi positif antara NLR dengan CRP di antara bayi prematur dengan sepsis awitan dini adalah r=0,702, p=0,001. Bayi dengan sepsis awitan dini memiliki jumlah leukosit lebih rendah dibanding bayi non-sepsis (median; IQR, x103: 8,9 (6,3-13,8) vs 12,5 (10,1- 16,1); p=0,016). Neutrophil-to-lymphocyte ratio dan CRP lebih rendah pada kelompok sepsis dibanding non-sepsis. Simpulan, NLR memiliki korelasi positif kuat dengan CRP pada bayi prematur dengan sepsis awitan dini.